The Manifestation Of Digital Transformation Concept In Indonesian Logistic Firms - Muhammad Taufani; Anton Wachidin Widjaja (Jurnal Manajemen, 2023)
Digital transformation has become an important challenge for logistic firms to achieve competitive advantages. However, the digitization process's implications on a firm's performance still need to be fully understood since transitioning from one method to another creates specific challenges. This study examines the effects of digital transformation on logistic firm performance in Indonesia and looks at the process of organizational learning and innovation as determinants of digital transformation. This study uses a quantitative method with data from 165 respondents of logistic firms that have implemented digital technology in their business operations. The PLS method is used as a data analysis method. Results showed that digital transformation positively and significantly affects logistic firm performance. It was also found that organizational innovation significantly affects digital transformation, ultimately affecting logistic firm performance. Meanwhile, organizational learning capabilities showed no direct effects on digital transformation.